How costly was the crisis of the 1990s? : a comparative analysis of the deepest crises in Finland and Sweden over the last 130 years - Flores, Elena; Giudice, Gabriele; Hagberg, Thomas; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
In the 1990s the world economy was hit by a series of unusually deep crises with far-reaching consequences, the first of which occurred in Finland and Sweden. This paper compares the cost of the crisis of the 1990s with the costs caused by all major crises and depressions since the 1870s in the two Nordic countries. First, it constructs a crisis chronology for Finland and Sweden. Second, it estimates the cost of every major crisis in terms of real income, industrial production and employment foregone. The numerical results demonstrate the severity of the crisis of the 1990s. It is one of the worst crises that have hit the two Nordic countries, on a par in several respects with the crisis of the 1930s, commonly regarded as the greatest crisis in modern history. The crises of the 1990s in Finland and Sweden were as severe as those that hit the world during the exceptionally crisis-ridden interwar period. However, the output losses in both countries during World War I and II remain higher than those of any peacetime crisis, notwithstanding Sweden's neutrality in both wars.
Economic Papers